STUDY THE IMMUNO POTENCY OF P. multocida ANTIGEN ON EXPERIMENTAL ANIMALS - صالح, ضحى; كاظم, سراب; شبر, إسماعيل (Iraqi Journal of Science, 2024)
The current study was designed to assess the immune potency of whole cell killed antigen of Pasteurella multocida prepared from 1ocal strains isolated from satisfactory cases (infected lung from sheep and goat), as it is necessary to know the local species deployed for use in the preparation of an effective vaccine, rather than vaccines prepared from standard isolates . The aim of this study is evaluate the immune potency of prepared antigen through its injection intraperitoneally in mice (0.5ml/moues) for two doses, protection being judged by the ability of immunized mice to survive challenge infection with virulent homologous microorganisms. Protective activity was achieved 65%, while the control group lost all animals.